Cultuurtransfer en het tijdschriftenonderzoek - Marjet Brolsma (Contextes)
In the current article the concept of cultural transfer is explored as a transnational approach for the study of periodicals. Cultural transfer is a useful perspective to situate national debates in a larger, European context. The approach is valuable for researching both the processes of cultural transfer and of acculturation within periodicals. In the first two sections the development and core assumptions of cultural transfer and the concept histoire croisée or ‘entangled history’ will be discussed and criticized. In what follows the relevant insights for the study of periodicals will be designated and subsequently translated into to a workable methodology.